A Nonparametric Peak Finder Algorithm and Its Application in Searches for New Physics. (29th December 2013) - Chekanov, S. V.; Erickson, M.
Abstract : We have developed an algorithm for nonparametric fitting and extraction of statistically significant peaks in the presence of statistical and systematic uncertainties. Applications of this algorithm for analysis of high-energy collision data are discussed. In particular, we illustrate how to use this algorithm in general searches for new physics in invariant-mass spectra using p p Monte Carlo simulations.